Chiral mesoporous silica synthesized by a facile strategy for loading and releasing poorly water-soluble drug. (2nd July 2020) - Gao, Zibin; Lv, Xiaoqian; Fu, Yufei; Zang, Xianghuan; Sun, Yongjun; Li, Shuo; Zhang, Huimin; Qiao, Shanlin; Wang, Long; Sun, Yanping
Abstract: Most of the mesoporous chiral mesoporous silica (CMS) was synthesized by the chiral surfactant-directing method. In this study, a facile method was designed to synthesize CMS. In this method, achiral amphiphile was used as templating agents, and dilute ammonia solution was applied to induce the chirality of the CMS. Meanwhile, its morphology can be controlled by changing the concentration of the aqueous ammonia solution. The obtained CMS was characterized by dynamic light scattering (DLS), X-ray diffraction (XRD), transmission electron microscopy (TEM), and scanning electron microscopy (SEM). The results showed that all of the CMS possessed highly ordered mesostructures, and as the concentration of ammonia decreases, the chirality of the CMS becomes more obvious. Water-insoluble drug curcumin (Cur) was used as a model drug. The characteristics of CMS before and after drug loading were further detected by Fourier transform infrared spectrometer (FT-IR), N2 adsorption–desorption and differential scanning calorimetry (DSC). The result showed that Cur was successfully loaded inside the pores of the CMS and remained an amorphous state due to steric inhibition. Additionally, CMS could significantly increase the release rate of Cur under different pH conditions.